The Influence Of E-Service Quality, E-Payment, And Web Design Quality On Customer Satisfaction In Purchasing Gacoan Noodles Through The Shopeefood Application - Dwi Putri Kinasih; Kussudyarsana Kussudyarsana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study was to analyze the effect of E-Service Quality, E-Payment, and Web Design Quality on customer satisfaction in purchasing Gacoan Noodles through the Shopeefood application in Surakarta City. This type of research is quantitative with explanatory research. The population in this study were all Gacoan consumers in Surakarta city. The sampling technique in this study. using purposive sampling. The sample calculation uses the theory of Ferdinand. The sample of this study amounted to 200 respondents. This study uses primary data in its preparation. Primary data is obtained through the first source or respondent answers from Gacoan Noodle customers in Surakarta City using a questionnaire. The results of this study show that the E-Service Quality variable has a positive influence on Customer Satisfaction with Gacoan products is a significant result. The ease and security of the payment process can affect customer satisfaction. Web Design Quality variable has a positive influence on Customer Satisfaction. The three independent variables (E-Service Quality, E-Payment, and Web Design Quality) together have a positive effect on Customer Satisfaction, indicating that service and a holistic shopping experience are key to increasing customer satisfaction.